Global Health Master’s Students: Demographics and Career Goals - Doobay-Persaud, Ashti A.; Galvin, Shannon R.; Sheneman, Natalie E.; Murphy, Robert L. (Frontiers in Education, 2017)
The Master of Science in Global Health (MSGH) at Northwestern University is a new competency-based graduate degree program designed to prepare students for careers in global health. The purpose of our research is to determine the market characteristics for this degree, provide student backgrounds that will guide curricular and programmatic improvements, and determine if these students intend to pursue degrees in global health. This study examines survey responses from students admitted to the MSGH program between 2014 and 2015. Survey data were collected by the Northwestern University School of Professional Studies (SPS) as part of the online admissions application process. During the same period, all active students in the program were invited to complete a separate, online survey asking about their global health experience, skills and career goals. Application responses were analyzed using descriptive statistics. Free-text responses from the survey were hand-coded using 10 categorical variables developed through an inductive process. Fifty-four individuals were admitted to the MSGH program within 12 months of its inception. Of these 78% were female and the average age was 36. Of those who responded to questions about current employment, 57% were working in a health science field, 11% in government or public administration, and less than 10% responded in all other categories. Responses from the online survey revealed that most students had some prior global health experiences primarily in the medicine and mission/volunteer categories, 45% and 50% respectively. Responses regarding career aspirations were spread evenly across categories and nearly all students intended to join the global health workforce. Medicine was identified most frequently as a desired field for future careers (30%), followed by government and policy (25%). The wide variety of disciplines represented in students’ previous work histories underscores and supports the interprofessional nature of the field and the workforce. This diversity extends to both educational backgrounds and prior field experience and necessitates pedagogical techniques that can appeal to a wide array of students, particularly a majority female population. Findings regarding desired future employment suggests that career advising will need to adapt to market demands, prioritizing project and program management related careers.